(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents methods of using information technology achievements in the conduct of the course “projective geometry”, which is passed to students studying in the mathematical direction of Higher Education. In particular, the possibilities of the “GeoGebra” program in visualizing three-dimensional shapes and performing various geometric actions on them are covered. GeoGebra can help solve complex projective geometry problems associated with perspective, duality, and homography by providing a dynamic visual representation of problem parameters. In addition, its convenient interface and presence on various platforms simplify the process of studying and applying the concepts of projective geometry. In general, GeoGebra is a valuable tool for students and researchers interested in projective geometry.